Stopping contagion with bailouts: Micro-evidence from Pennsylvania bank networks during the panic of 1884 - Anderson, Haelim Park; Bluedorn, John C. (Journal of Banking & Finance, 2017)
Using a newly constructed historical dataset on the Pennsylvania state banking system, detailing the amounts of “due-froms” on a debtor bank-by-debtor bank basis, we investigate the effects of the Panic of 1884 and subsequent private sector-orchestrated bailout of systemically important banks (SIBs) on the broader banking sector. We find evidence that Pennsylvania banks with larger direct interbank exposures to New York City changed the composition of their asset holdings, shifting from loans to more liquid assets and reducing their New York City correspondent deposits in the near-term. Over the long-term though, only the lower correspondent deposits effect persisted. Our findings show that the banking turmoil in New York City impacted more exposed interior banks, but that bailouts of SIBs by the New York Clearing House likely short-circuited a full-scale banking panic.